2018
DOI: 10.21873/invivo.11386
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of Type 1 Angiotensin II Receptor Inhibits T-lymphocyte Activation and IL-2 Production

Abstract: Background/Aim: Novel information on the role of endogenous compounds in regulating physiological and pathological process are of interest, as it may lead to the development of better strategies for disease management. The role of angiotensin II and the signaling of type 1 angiotensin II receptor (AGT1R) in T-lymphocyte activation and interleukin-2 (IL-2) production are largely unknown. Materials and Methods: Jurkat T-cells were treated with AGT1R inhibitor candesartan and stimulated with phorbol myristate ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Ang II has been shown to play a role in regulating the immune system ( Figure 4 ). In fact, AT1R is found on the surface of a variety of immune cells, including T cells, which possess endogenous RAS, express functional RAS components, and locally produce Ang II [ 42 , 43 , 44 ]. The latter promotes immune cells’ proliferation, migration, differentiation, adhesion, and effector function, and acts as a costimulatory molecule important for T-cell activation.…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Ang II has been shown to play a role in regulating the immune system ( Figure 4 ). In fact, AT1R is found on the surface of a variety of immune cells, including T cells, which possess endogenous RAS, express functional RAS components, and locally produce Ang II [ 42 , 43 , 44 ]. The latter promotes immune cells’ proliferation, migration, differentiation, adhesion, and effector function, and acts as a costimulatory molecule important for T-cell activation.…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%
“…The proportion of patients with elevated levels of these proteins in the severe group was significantly higher than in the mild group [ 41 ]. Tawinwung et al have shown that AT1R signaling is essential for T-cell activation and IL-2 production, and the inhibition of this pathway suppressed T-cell activation via an ERK-dependent mechanism [ 43 ].…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%
“…Furthermore, candesartan inhibits inflammation by modulating signaling cascades dependent on TNF-α, IL-1beta, IL-2, IL-6, TGF-β, and NF-κB. In addition, it reduces the formation of ROIs by phagocytes and lowers the expression of CD25 and IL-2 release by T cells [113,[124][125][126][127][128][129]. However, this medicament seems to not affect the secretion of IL-10 [130], similarly to olmesartan [121].…”
Section: Candesartan Irbesartanmentioning
confidence: 99%
“…-IL-1beta [31], IL-6 and IL-8 concentration [31,32,85]; -CRP concentration [41]; -TNF-alfa concentration [41,113,[124][125][126][127][128][129]; -lymphocyte proliferation and IFN-gamma production in vitro assays, and suppressed antigen-specific Th1 and Th2 lymphocytes in vivo [115]; -formation of ROIs by phagocytes [113,[124][125][126][127][128][129]; -the expression of CD25 and IL-2 release by T cells [113,[124][125][126][127][128][129]; -the general number of immune cells in bronchoalveolar lavage fluid [125]; -the release of Th2-lymphocyte (IL-4, IL-5 and IL-13) and Th1-lymphocyte (IL-2 and IFN-γ) cytokines [125].…”
Section: Reduction Inmentioning
confidence: 99%
“…A previously-published study has reported that downregulation of ACE2 in macrophages in COVID-19 patients increases the inflammatory cytokine and production of NO. On the other hand, Ang II induces cell proliferation and cytokine production implying the role of Ang II in regulating the cell signaling in inflammation and immune-related diseases [186]. IL-2 is an immune cytokine that stimulates the proliferation of T cells [187].…”
Section: Link Between Immune Responses and Renin-angiotensin System (...mentioning
confidence: 99%